PEKERJA PEREMPUAN PADA PTPN V KEBUN SEI LINDAI TERHADAP KESEJAHTERAAN KELUARGA DI KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Simatupang, Yuni Paradetama; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Female contractors at the PTPN V Sei Lindai Plantation are currently dominated by house wives. Unfortunately, they don't care about their children's education. This can be seen when they work, some of them sometimes bring their children to work. The childis no longer in school because the family's economy is not sufficient. Even thought he school located in the plantation area is a stateschool. The school does not make it too difficult for parents to pay tuition fees per month. It also needs to be considered by the Company so that the Contractors are more enthusiastic in working and sending their children to school. The purpose of this study was to determine the time spent by female workers at work and to find out the monthly wages of female contractors. The main theory is social welfare theory, the other supporting theory is family sociology theory. This research uses descriptive quantitative analysis method with the type of survey research based on the location and situation of the object. The results of the study concluded that 64% of female workers devoteonly 8 hours of work time, after returning home from work they return home. It can be seen that most of the time spent by female workers is with their families at home. The wages received by female workers each month are in the rangeof 2-3 million. The wages received dependon the random production that is done.Keywords: FemaleWorkers, Contractors, FreeTime